2019
DOI: 10.1038/s41598-019-51380-w
|View full text |Cite
|
Sign up to set email alerts
|

Insights into replicative senescence of human testicular peritubular cells

Abstract: There is evidence for an age-related decline in male reproductive functions, yet how the human testis may age is not understood. Human testicular peritubular cells (HTPCs) transport sperm, contribute to the spermatogonial stem cell (SSC) niche and immune surveillance, and can be isolated and studied in vitro. Consequences of replicative senescence of HTPCs were evaluated to gain partial insights into human testicular aging. To this end, early and advanced HTPC passages, in which replicative senescence was indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 76 publications
6
46
2
Order By: Relevance
“…Peritubular cells, perivascular cells, and ALCs express NR2F2. For PDGFRα, of which the expression was observed at the same locations as NR2F2, our results differ partly from other studies where PDGFRα expression in the adult human testis is described for peritubular cells, 24,30 spermatids, 24 or Sertoli and Leydig cells 31 . This suggests that PDGFRα immunostaining in the human testis is highly variable, presumably depending on the antibody source and staining protocol used.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Peritubular cells, perivascular cells, and ALCs express NR2F2. For PDGFRα, of which the expression was observed at the same locations as NR2F2, our results differ partly from other studies where PDGFRα expression in the adult human testis is described for peritubular cells, 24,30 spermatids, 24 or Sertoli and Leydig cells 31 . This suggests that PDGFRα immunostaining in the human testis is highly variable, presumably depending on the antibody source and staining protocol used.…”
Section: Discussioncontrasting
confidence: 96%
“…The current study further shows that THY1, one of the markers to identify MSCs according to the minimal criteria, 32 is expressed by peritubular cells and perivascular cells in the adult human testis, and not by ALCs. This is in line with studies on human peritubular cells where expression of THY1 was found 30,33 . The co‐expression of PDGFRα and THY1 immediately after isolation and following propagation of the cells in vitro confirmed the immunohistochemical localization results that the THY1 + cells might be a subpopulation of the PDGFRα + cells.…”
Section: Discussionsupporting
confidence: 89%
“…Testicular biopsies for HTPC isolation and for immunohistochemistry were obtained from men 36-55 years of age (in total n = 11) with obstructive azoospermia but normal spermatogenesis as described [5,9,13]. The study was approved by the local Ethics Committee (Technical University of Munich, Faculty of Medicine; project 491/18S-KK), and scientific use of the cells was permitted by written informed consent from all of the patients.…”
Section: Human and Monkey Samplesmentioning
confidence: 99%
“…Peritubular cells are also cells of the human testis that can be isolated and examined in vitro [5][6][7]. As the in situ characteristics of peritubular cells are well maintained and characterized in vitro [7][8][9], studies in these human testicular peritubular cells (HTPCs), in conjunction with human testicular sections, provide a unique experimental window into the human testis.…”
Section: Introductionmentioning
confidence: 99%
“…Episode-like pulse testosterone supplementation therapy induces tumor senescence and growth arrest down-modulating androgen receptors through its effect on ERK1/2 signaling [73]. Interestingly, recent studies by Schmidt et al [74] reported that cellular senescence in human testicular peritubular-myoid cells is not associated with a decreased expression of crucial genes (contractility markers and androgen receptor). However, striking morphological changes in these cells are accompanied by altered cellular protein levels.…”
Section: Discussionmentioning
confidence: 99%